Benign Paroxysmal Positional Vertigo After Pediatric Sports-Related Concussion. Issue 4 (July 2020) - Reimer, Karen; Ellis, Vanessa; Cordingley, Dean M.; Russell, Kelly; Ellis, Michael J.
Abstract : Objective: Report the clinical findings and outcomes among pediatric patients diagnosed with benign paroxysmal positional vertigo (BPPV) after sports-related concussion (SRC). Design: Retrospective case series. Setting: Multidisciplinary pediatric concussion program. Patients: Patients younger than 19 years with a sport or recreation activity–related concussion referred for comprehensive vestibular physiotherapy assessment. Main outcome measure: Symptom resolution after targeted particle repositioning (PR). Results: During the study period, 115 pediatric SRC patients underwent vestibular physiotherapy assessment including 12 (10.4%) who were diagnosed with BPPV. Unilateral posterior semicircular canal (SCC) BPPV was diagnosed in 8/12 (75%) patients, and unilateral anterior SCC BPPV diagnosed in 4/12 (25%) patients. Benign paroxysmal positional vertigo was successfully treated in all patients with a mean of 1.58 targeted PR maneuvers (range = 1-4). Conclusions: Comprehensive management of pediatric SRC requires a multidisciplinary approach to address the heterogeneous pathophysiology of persistent postconcussion symptoms. Pediatric SRC patients with coexisting BPPV should be considered for targeted PR.